Implications of using small meshed gillnets for the sustainability of fish populations: a theoretical exploration based on three case studies. (October 2015) - Wolff, M.; Taylor, M. H.; Tesfaye, G.
Abstract The study explores the impacts of varying gillnet mesh size and fishing level on yield per recruit (Y/R), escapement spawning stock (ESS) and mega‐spawners (MS) of three widely distributed freshwater fishery target species. Y/R is maximised when the optimal length of capture (Lcap) is above the size of maturity (L50). However, the unimodal shape of gillnet selectivity results in lower impacts to ESS and MS with both smaller and larger mesh sizes. Under conditions of moderate exploitation, the fraction of MS was significantly larger if small meshed gillnets were used. This is due to the relatively smaller cumulative vulnerability from small mesh sizes through time, as they target a smaller size range of fish, which also grow more quickly through the vulnerable window due to higher growth rates. Therefore, unlike trawls and beach seines, which select all size classes beyond the minimum length of capture (Lc), small meshed gillnets are not necessarily destructive and may rather promote sustained production by allowing a higher proportion of the spawning biomass to remain in the stock. The work also helps to explain the observation of sustained fish production in many developing countries despite the persistent use of gillnets of small mesh size that target small, under‐sized individuals.